Will the National Disability Insurance Scheme Improve the Lives of those Most in Need? Effective Service Delivery for People with Acquired Brain Injury and other Disabilities in Remote Aboriginal and Torres Strait Islander Communities. Issue 2 (23rd June 2014) - Stephens, Anne; Cullen, Jennifer; Massey, Libby; Bohanna, India
Abstract : The aims of National Disability Insurance Scheme (NDIS) are to provide long‐term, person‐centred care and support to all Australians with a significant and ongoing disability, including individuals with an acquired brain injury (ABI). The scheme has significant potential to provide equitable opportunity of access to health and disability services. Historically, however, service provision in remote and outer regional areas of Australia lags behind more densely populated centres. Aboriginal and Torres Strait Islanders living with disability are already significantly marginalised. Further to this, people with an ABI are very often misunderstood and overlooked by disability services, health professionals and governments, and frequently fall victim to the criminal justice system. This paper provides an overview of the state of ABI disability for Aboriginal and Torres Strait Islanders in remote and outer regional settings, and the present sets of barriers they face to obtaining quality care and effective interventions. A significant opportunity has emerged with the advent of the NDIS but equitable benefit can only be achieved if additional and specialised measures are devised and implemented to appropriately screen for, and assess, incidence of ABI; disability services are appropriately resourced to overcome the pre‐existing disadvantage, and education, training and recruitment of Aboriginal and Torres Strait Islanders with the NDIS is undertaken to lead attitudinal changes in community to disability and health services. This paper concludes with recommendations for the NDIS to meet its laudable objectives.